Financial Feasibility and Risk Analysis of a 4-Star Hotel Development at PT Bukit Asam’s Wisma Ombilin - Berlyan Besoni; Sudarso Kaderi Wiryono (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study proposes transforming PT Bukit Asam’s underutilized Wisma Ombilin land into a modern 4-star hotel to diversify revenue, reduce coal dependency, and align with sustainability goals. Located in Padang City, the project aims to boost economic value, create jobs, and support local growth. Combining qualitative and quantitative methods, the research analyzes Padang’s hotel market, financial feasibility, and project risks. Market analysis reveals strong demand for 4-star hotels, with post-pandemic occupancy rates and room prices surpassing pre-pandemic levels. Financial modeling estimates a Net Present Value (NPV) of RP 188.38 billion, an Internal Rate of Return (IRR) of 16.38%, and a payback period of 10.9 years, indicating solid profitability. Sensitivity analysis identifies key risks related to room rates, occupancy, and interest rates, recommending dynamic pricing and financing strategies for mitigation. Strategic risk management includes disaster-resilient design and operational efficiencies. The project supports PTBA’s transition from coal reliance, improves ESG performance, and enhances competitiveness. With strong market potential and effective risk controls, the hotel development offers sustainable returns and stakeholder value, warranting progression to detailed planning and financing.